Titanium Dioxide: Kinetically Favorable Vapor–Adsorbate–Solid Growth of Rutile Nanowires (Small Methods 7/2019). Issue 7 (8th July 2019) - Xie, Dong Yue; Lin, Ming‐hui; Zhou, Wei; Wang, Jian; Zhu, Guo‐zhen
Abstract : The cover for article number 1900111 by Guo‐zhen Zhu and co‐workers represents vapor‐adsorbate‐solid growth for single‐crystal oxide nanowires. The growth dynamics are highlighted by the motional oxide gas phases (floating blue balls) from an oxide substrate (in blue) in a quartz tube, the adsorbates (blue thin covers) at metal seeds, and the growing nanowires with tunable shape due to different seeds (gold and silver are in yellow and white, respectively).